Statistical analysis of timber–concrete connections – Mechanical properties. (15th July 2015) - Dias, A.M.P.G.; Martins, A.R.D.; Simões, L.M.C.; Providência, P.M.; Andrade, A.A.M.
Abstract: In this paper a statistical analysis was done, to assess the most adequate statistical distributions and corresponding parameters for the timber–concrete connection properties, aiming linear and non linear analysis. The properties considered for the linear analysis were the load–slip modulus and load carrying capacity. For the non-linear analysis five mathematical models were selected to describe the connection load–slip behavior. The models were fitted to the load–slip curves available in the references. The obtained parameters were subjected to a statistical analysis in order to assess the most adequate statistical distributions. On this analysis the whole set of suitable results available included more than 1000 single test results to have a sample as broad as possible. A chi-square goodness-of-fit with a 5% of significance level were performed to selected distributions, in most of the situations the normal distribution was found to be adequate. Furthermore, for most of the connection types good load–slip descriptions could be obtained with the 3 parameter models.